Musculoskeletal Manifestations of Non-RA Connective Tissue Diseases: Scleroderma, Systemic Lupus Erythematosus, Still's Disease, Dermatomyositis/Polymyositis, Sjögren's Syndrome, and Mixed Connective Tissue Disease - Jacques, Thibaut; Sudoł-Szopińska, Iwona; Larkman, Neal; O'Connor, Phil; Cotten, Anne (Seminars in Musculoskeletal Radiology, 2018)
The most common systemic rheumatologic conditions are connective tissue diseases (including rheumatoid arthritis [RA]) followed by spondyloarthropathy. With the advent of biotherapies and imaging biomarkers, development in the imaging of RA and spondyloarthropathies has received substantial attention in the literature. This article details the various musculoskeletal imaging features of the other connective tissue diseases such as scleroderma and progressive systemic sclerosis, systemic lupus erythematosus, Still's disease, dermatomyositis and polymyositis, Sjögren's syndrome, and mixed connective tissue disease.
Keywords: scleroderma; lupus; dermatomyositis; polymyositis; Sjögren's syndrome